English foreign language learners’ reluctance to speak English in higher education - Fakhrurrazi; M. Fadli; Nasruddin (Englisia: Journal of Language, Education, and Humanities, 2026)
Reluctance to speak English remains a persistent challenge for English as a Foreign Language (EFL) learners in higher education, where oral participation is essential for academic engagement and communicative competence. Despite years of formal instruction, a considerable number of university students continue to avoid English communication, suggesting that their reluctance extends beyond purely linguistic limitations. This study investigates the characteristics and determinants of EFL students' reluctance to speak English, with particular attention to the interplay of affective, linguistic, and contextual factors. Employing a mixed-methods design, data were collected from undergraduate EFL students at four public universities in Indonesia using a structured questionnaire containing Likert-scale items. Quantitative data were analyzed through descriptive statistics, while qualitative responses were examined using inductive thematic analysis. The findings indicate that students' speaking reluctance is a multifaceted phenomenon predominantly shaped by speaking anxiety, fear of negative evaluation, diminished self-perceived communicative competence, and instructional approaches that prioritize accuracy over interaction. Silence emerged as a context-dependent, psychologically motivated response rather than an indicator of disengagement. Institutional expectations, hierarchical classroom dynamics, and limited opportunities for low-risk oral practice further exacerbated learners' reluctance. This study advances EFL speaking research by conceptualizing speaking reluctance as an affective-interactional dimension closely linked to willingness to communicate and classroom silence in higher education settings. Pedagogically, the findings underscore the necessity for anxiety-sensitive instruction and the creation of psychologically safe communicative environments.